Effect of Normal Force, Sliding Speed, Temperature, and Al₂O₃ Addition on Wedge and Conventional Disc Brake Performance - Sayed, Eman G.; Makrahy, Mostafa M. M.; Sharkawy, Mohamed R.; Gawwad, Khalid A. A. (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2025)
The investigation probed the structure of the material of the brake shoe, the roughness of the surface, and wear behavior to understand its influence on system efficiency. Regression analysis and Design of Experiments (DOE) were utilized to examine dependencies of variables. The findings indicate that Al₂O₃ significantly improves thermal stability and wear in wedge-type and disc brakes. In addition, the optimal choice of sliding velocity, normal load, and temperature can produce better braking and reduced wear. These results are important in developing more efficient and durable brake systems for automotive, aerospace, and industrial applications. The study also emphasizes the importance of the design and material composition of brake shoes for obtaining ultimate brake performance under several operating conditions.